Prevalence and antibiotic susceptibility profiles of campylobacter, staphylococcus aureus, salmonella and E.coli from chicken carcasses - Abu Ramouz, Jawaher; Shahateet, Reham; Daraweesh, Layan; Rjoub, Sireen (Palestine Polytechnic University)
Several studies implicated that contamination of poultry carcasses in abattoirs is considered a significant source of human infections. Campylobacter, Salmonella, E.coli and Staphylococcus aureus are among the high prevalent pathogens causing foodborne diseases. However, due to the random and inefficient use of antibiotics in poultry, such pathogens are increasingly resistant to the clinically important antibiotics and this rising resistance is a concern for public health. This study aimed to compare the Presence and antimicrobial susceptibility of Campylobacter, Salmonella, E. coli and S. aureus species in chicken carcasses. Four samples were collected from a poultry farms in (Dora and Hebron), Bacteria strains were isolated and recognized using selective and deferential media. Isolates were then tested for sensitivity to Azithromycin, Ampicillin, Tetracycline, Gentamicin, and Nalidixic Acid antibiotics using the Kirby-Bauer disk diffusion test with reference of the Clinical and Laboratory Standards Institute (CLSI). Results indicates the highest level of resistance among Campylobacter (n=19) tested was to Nalidixic Acid (NA) 100%, Tetracycline and Azithromycin (AZM) 94%,It showed moderate resistance to a Gentamycin 10.5 %, and Ampicillin 26.3% While Salmonella (n=6) bacteria showed highly 100 % resistance to AM, NA, also 67 % to AZM. While its highly sensitive to CN antibiotic. For S. aureus (n=9), disc diffusion testing showed 100% correlation with agar dilution for (TE) and (NA), and 89% AZM. A high level of sensitivity 100% to AZM, CN and 16.6% to AM was found in the E.coli isolates (n=6) by disc, whereas 83 % of isolates were resistance to AM, 50% to NA and low level 33.3% to TE. Overall, our study has emphasize on minimize the misuse of available antimicrobials in agriculture and medicine, this would aid to easily control and eliminate these bacteria, and to lower farmer's material losses as well the risk of its impact on humans.
2017 , Applied Biology
Keywords: antibiotic susceptibility; Multi drug resistanc; Campylobacter